2024
DOI: 10.1002/cbic.202300784
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glycosylated nucleosides in small synthetic glyco‐RNAs

Frank St. Michael,
Maha Ben Hamouda,
Jacek Stupak
et al.

Abstract: Recently, the post‐transcriptional modification of RNA with N‐glycans was reported, changing the paradigm that RNAs are not commonly N‐glycosylated. Moreover, glycan modifications of RNA are investigated for therapeutic targeting purposes. But the glycoRNA field is in its infancy with many challenges to overcome. One question is how to accurately characterize glycosylated RNA constructs. Thus, we generated glycosylated forms of Y5 RNA mimics, a short non‐coding RNA. The simple glycans lactose and sialyllactose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…1 Recent research using blotting electrophoresis of RNA extracted from cells showed that small RNAs on the living cell surface were Nglycosylated and terminated with sialic acids (Sias). 7 Mass spectrometry, 8 high-performance anion-exchange chromatography, 9 and RNA sequencing 10 were also applied to the in vitro detection of glycoRNA. However, these in vitro analysis techniques discarded the location information on the sialylated RNA and could not provide the number of the glycosylation sites or the potential functions of the glycosylated RNAs (glycoRNAs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…1 Recent research using blotting electrophoresis of RNA extracted from cells showed that small RNAs on the living cell surface were Nglycosylated and terminated with sialic acids (Sias). 7 Mass spectrometry, 8 high-performance anion-exchange chromatography, 9 and RNA sequencing 10 were also applied to the in vitro detection of glycoRNA. However, these in vitro analysis techniques discarded the location information on the sialylated RNA and could not provide the number of the glycosylation sites or the potential functions of the glycosylated RNAs (glycoRNAs).…”
Section: ■ Introductionmentioning
confidence: 99%